2008
DOI: 10.4067/s0717-95022008000200006
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Morphology and Frequency of the Vomeronasal Organ in Humans

Abstract: The vomeronasal organ was first described in humans in the seventeenth century. It has a chemosensory function and is found in the mucosa of the nasal septum of mammals and consists of an opening in the mucosa at the base of the nasal septum. For this study, 143 individuals undergoing nasofibrolaryngoscopy were studied, and presence of the vomeronasal organ was considered to be a finding from the examination. Three morphological types of vomeronasal organ were observed: fissure, fossette and circular. The tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although a constant incidence has been found in different adult populations around the world (Bulgaria, Canada, Egypt, France, Mexico, and the United States of America), studies have shown it to be present (at least unilaterally and predominantly on the left side) in around one third of the population [ 9 - 11 , 15 - 18 ]. Reports suggest that it is more commonly found in children [ 6 , 16 - 18 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a constant incidence has been found in different adult populations around the world (Bulgaria, Canada, Egypt, France, Mexico, and the United States of America), studies have shown it to be present (at least unilaterally and predominantly on the left side) in around one third of the population [ 9 - 11 , 15 - 18 ]. Reports suggest that it is more commonly found in children [ 6 , 16 - 18 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although a constant incidence has been found in different adult populations around the world (Bulgaria, Canada, Egypt, France, Mexico, and the United States of America), studies have shown it to be present (at least unilaterally and predominantly on the left side) in around one third of the population [ 9 - 11 , 15 - 18 ]. Reports suggest that it is more commonly found in children [ 6 , 16 - 18 ]. Some studies claim that it is present in over two-thirds of young people, with an increased incidence bilaterally, whilst other researchers suggest that it is present on both sides of the septum in almost all newborn babies [ 14 , 18 - 19 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation